Efficacy and safety of ultrasound-guided pulsed radiofrequency in the treatment of the ophthalmic branch of postherpetic trigeminal neuralgia - Li, Fubo; Gong, Gege; Zhang, Yue; Ou, Cehua (Frontiers in Neurology, 2024)
Abstract Objective: To investigate the efficacy and safety of ultrasound-guided pulsed radiofrequency (PRF) targeting supraorbital nerve for treating the ophthalmic branch of postherpetic trigeminal neuralgia. Methods: A retrospective cohort study was conducted involving patients who presented at the Department of Pain, Affiliated Hospital of Southwest Medical University from January 2015 to January 2022. The patients were diagnosed with the first branch of postherpetic trigeminal neuralgia. In total, 63 patients were included based on the inclusion and exclusion criteria. The patients were divided into the following two groups based on the treatment method used: nerve block (NB) group (n = 32) and PRF + NB group (radiofrequency group, n = 31). VAS scores, PSQI scores, and dose of pregabalin taken before and after treatment were compared between the two groups. Results: The postoperative VAS score, PSQI score, and pregabalin dose were significantly decreased in both groups. Furthermore, significant differences were found between the two groups at each time point preoperative and postoperative (P < 0.05). After 6 months of treatment, the excellent rate of VAS score in the radiofrequency group was 70.96% and the overall effective rate was 90.32%, which was higher than that in the NB group. The difference in the efficacy was statistically significant (P < 0.05). Conclusion: PRF targeting the supraorbital nerve can effectively control the pain in the first branch of the trigeminal nerve after herpes, enhance sleep quality, and reduce the dose of pregabalin.